The hospitalized old patients personas support system under the Peplau’s theory purposes - Santos, Silvana Sidney Costa; Henriques, Maria Emília R. de Miranda (Rev Rene, 2000)
This study aimed to map the personal support network of hospitalized old patients using the Peplau’s theory presupposes about interpersonal relations. An exploratory and descriptive design was adopted under a quantitative and qualitative approach. The sample was constuttuted by 60 hospitalized old patients from the public health system of Recife-PE. We used a form which was adapted from the BOAS’ questionnaire during the period of 6.11.1996. The findings indicated that the most important persons for old people are their neighbors and friends (31,6%). Thus, it is the nurses’ responsibility to identify this network support group for old people in order to prevent the social isolation.